Sociology of childhood and Latin American as its locus of enunciation - Natalia Sepúlveda-Kattan (Íconos)
This theoretical article poses a dual theoretical challenge to contemporary practitioners of the sociology of childhood in Latin America: a) to take a critical stance vis a vis the scarce and weak attention that sociology has given to childhood as a social fact; and b) take a critical posture regarding the discipline itself, in an effort to open the door for a more adequate consideration of how the multiple Latin American childhoods exist in colonial contexts. A review of the relevant literature enables a systematization of the potential components of a critical sociology of childhood, and those that would allow to consider this object of study from the authors´ particular locus of enunciation. Texts from decolonial and critical thinkers, who have highlighted the importance of situated thought, -especially insofar as it allows speech coming from an identifiable specific location-, were studied. The article examines approaches from classical authors in the sociology of childhood and works by Latin American writers, who have tackled the specific problems which studying infancy poses in this continent. Consideration is given to the challenges this disciplinary field confronts nowadays. An adequate observation of childhood in Latin America requires articulating both decolonial thought and the sociology of childhood itself. However, finding a common ground between these two fields requires that the inner tensions inherent to decolonial thought be confronted and seriously considered. Likewise, it is argued that a suitable knowledge about the different Latin American childhoods could bring about deep changes in current paradigms through which contemporary societies are understood.